2023
DOI: 10.1039/d3ra02788k
|View full text |Cite
|
Sign up to set email alerts
|

Benzophenones-natural metabolites with great Hopes in drug discovery: structures, occurrence, bioactivities, and biosynthesis

Sabrin R. M. Ibrahim,
Duaa Fahad ALsiyud,
Abdulrahman Y. Alfaeq
et al.

Abstract: Fungi have protruded with enormous development in the repository of drug discovery, making them some of the most attractive sources for the synthesis of bio-significant and structural novel metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…Moreover, the authors showed that these pigments removed phenyl-Hg + ions from aqueous solution [ 52 ]. Sulochrin and related benzophenones ( detected in the extracts of metal-treated P. velutinum ) have been reported as radical scavengers and antioxidants [ 53 ]. This indicates that the production of these compounds by the fungus can occur because of activation of the metal defense system.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the authors showed that these pigments removed phenyl-Hg + ions from aqueous solution [ 52 ]. Sulochrin and related benzophenones ( detected in the extracts of metal-treated P. velutinum ) have been reported as radical scavengers and antioxidants [ 53 ]. This indicates that the production of these compounds by the fungus can occur because of activation of the metal defense system.…”
Section: Resultsmentioning
confidence: 99%